EVALUASI PELAKSANAAN PROGRAM PENGENDALIAN DBD DALAM MEMPERKUAT SURVEILANS DI KOTA MAKASSAR - Muttaqin, Muhammad Zainul; Yusriani; Batara, Andi Surahman (Rena Cipta Mandiri, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem in Makassar City and requires a strong surveillance system. This study aimed to evaluate the implementation of the Dengue Prevention and Control Program (P2DBD) in strengthening the dengue surveillance system in Makassar City. This study employed a descriptive qualitative evaluation approach involving 11 key informants from the Makassar City Health Office. Data were collected through in-depth interviews, observations, and document review and analyzed based on input, process, output, and outcome aspects. The findings indicate that the P2DBD program has been implemented fairly well; however, limitations remain in human resources, infrastructure, and preventive funding. Program implementation is still largely reactive. While most activities met program targets, their impact on reducing dengue cases was limited. Nevertheless, improvements were observed in early case detection and intersectoral coordination. In conclusion, strengthening the dengue surveillance system in Makassar City requires improvements in human resources, infrastructure, preventive financing, community participation, and more proactive surveillance methods.